Exploring Teenager’s Language Attitudes towards Javanese Language - Anna Fitriati; Diksita Galuh Nirwinastu; Haniel Arbert Tantio (Universitas Sanata Dharma, 2025)
Language attitudes significantly influence language vitality and revitalization, shaping users' language choices. In Indonesia, indigenous languages, including Javanese, are declining in use, particularly among younger generations who prefer Indonesian for daily communication. Family language policies, where parents prioritize Indonesian over indigenous languages, contribute to this trend. This study investigates teenagers’ language attitudes towards Javanese, aiming to inform strategies for preserving the language. Using a mixed-method sociolinguistic approach, the researchers collected data through surveys and interviews, examining factors like cultural identity, social dynamics, educational experiences, and media exposure. The study involves Junior High School students, with 127 survey responses and 42 respondents joining the interviews. The findings reveal that 44.1% of respondents learned Javanese as their mother tongue, while 55.1% acquired Indonesian. Proficiency in Javanese varies: 41.7% can fluently use Javanese Ngoko, but only 4.7% are fluent in Krama. Javanese Ngoko is mainly used within families and local communities, whereas Indonesian dominates in schools and public spaces, influenced by its perceived utility and globalization. Despite challenges, including limited learning resources and fear of misuse, respondents view Javanese positively, driven by cultural pride and ethnic identity. These findings highlight the need for targeted strategies to empower teenagers to preserve and revitalize Javanese. Addressing language attitudes and increasing exposure to Javanese could help reverse its decline.